2017
DOI: 10.5815/ijmsc.2017.01.01
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced E-recruitment using Semantic Retrieval of Modeled Serialized Documents

Abstract: Retrieval in existing e-recruitment system is on exact match between applicants" stored profiles and inquirer"s request. These profiles are captured through online forms whose fields are tailored by recruiters and hence, applicants sometimes do not have privilege to present details of their worth that are not captured by the tailored fields thereby, leading to their disqualification. This paper presents a 3-tier system that models serialized documents of the applicants" worth and they are analyzed using docume… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 2 publications
1
3
0
Order By: Relevance
“…AJS then offers a list of jobs combined with links to their correspondent employers to the Jobseeker. A similar study can be found in the work of Owoseni et al, [15] where they introduced a 3-tier electronic recruitment system which models serialized information of the applicants such as their income and social circumstances. The documents are analyzed using document retrieval and natural language processing in order to examine documents and applications just like humans would do.…”
Section: Introductionsupporting
confidence: 56%
“…AJS then offers a list of jobs combined with links to their correspondent employers to the Jobseeker. A similar study can be found in the work of Owoseni et al, [15] where they introduced a 3-tier electronic recruitment system which models serialized information of the applicants such as their income and social circumstances. The documents are analyzed using document retrieval and natural language processing in order to examine documents and applications just like humans would do.…”
Section: Introductionsupporting
confidence: 56%
“…Another system KELVIN [30] extracts entities and relations from large text collections. The core features of KELVIN are (1) cross-document entity co-references, (2) inter-document co-reference chains, (3) a slot value consolidator for entities, (4) the application of inference rules to expand the number of asserted facts and (5) a set of analysis and browsing tools supporting development.…”
Section: Knowledge Base Constructionmentioning
confidence: 99%
“…It utilizes a hybrid approach to combine existing Natural Language Processing (NLP) techniques with the new form of context-driven extraction techniques for extracting the layout, structure and content information of a job description. Owoseni et al [2] built a 3-tier technique using a semantic model. This technique performs analysis using document retrieval and natural language processing techniques for a human-like assessment.…”
Section: E-recruitment Systemsmentioning
confidence: 99%
See 1 more Smart Citation